SUPERVISI AKADEMIK KEPALA SEKOLAH BERBASIS COACHING MODEL GROW UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR - Rasmaladewi, Rasmaladewi; Rasyid, Sparta; Iskandar, Iskandar (Hijri, 2025)
This research aims to find out 1. To analyze the academic supervision planning of school principals based on the grow model coaching to improve the pedagogical competence of elementary school teachers in Baktiya sub-district, North Aceh. 2. To analyze the implementation of school principal academic supervision based on the grow model coaching to improve the pedagogical competence of elementary school teachers in Baktiya sub-district, North Aceh.3. To analyze the evaluation or follow-up of the principal's academic supervision based on the Grow model coaching in improving the pedagogical competence of elementary school teachers in Baktiya sub-district, North Aceh. This research method uses qualitative with a descriptive approach. Place and time of research at SD Negeri 5 and SD Negeri 6 Baktiya Barat and time in July 2024 at SD Negeri 5 and SD Negeri 6 Baktiya Barat. Data collection techniques using observation, interviews and documentation. Meanwhile, data analysis techniques include reduction, display, and conclusion drawing/verification. Research results: 1) results of program evaluation analysis and evaluation of the implementation of previous year's supervision as well as follow-up on supervision results. The madrasah head's academic supervision planning is prepared at the beginning of the school year, by first identifying problems, determining objectives and determining implementation times which are prepared in a precise schedule; 2) the implementation of academic supervision at this school uses direct supervision techniques, through class visits, carried out according to the schedule that has been prepared with the teacher. Visit to find out directly about the adjustments between learning planning and the direct learning process. The school principal also carries out follow-up activities to follow up on findings during supervision; 3) The results of the evaluation of the implementation of academic supervision are used to: Improve the supervision program in the following year, follow up on difficulties faced by teachers, find the right approach for each teacher with diverse characters and abilities.